Maternal stress and pediatric brain cancer: A French study. Issue 1 (2nd January 2019) - Labrell, Florence; Câmara-Costa, Hugo; Dufour, Christelle; Grill, Jacques; Chevignard, Mathilde
Abstract: Background: Despite evidence that pediatric cancer induces a trajectory of parental stress, studies including mothers of children with malignant brain tumors remain scarce. The present work aims to add to the scientific literature by evaluating maternal stress with a French translation of the Pediatric Inventory for Parents (PIP) in a population of mothers whose children have been diagnosed with a brain tumor. Procedure: The mothers of 35 children with malignant brain tumors completed the Pediatric Inventory for Parents (PIP), the State-Trait Anxiety Inventory (STAI) and the Family Assessment Device (FAD) at a mean time since diagnosis of 2.3 years. Results: The PIP showed good internal consistency and correlated significantly with the STAI and the FAD. Maternal stress scores were higher in younger mothers and in mothers of younger children. Emotional functioning was the most affected domain. Conclusions: Emotional stress as assessed by the PIP in mothers of children with malignant brain tumors is considerable, and should be routinely assessed, in order to implement appropriate specific psychosocial interventions when needed.